Extending the low-recycling, flat temperature profile regime in the lithium tokamak experiment-β (LTX-β) with ohmic and neutral beam heating. (1st May 2023) - Boyle, D.P.; Anderson, J.; Banerjee, S.; Bell, R.E.; Capecchi, W.; Elliott, D.B.; Hansen, C.; Kubota, S.; LeBlanc, B.P.; Maan, A.; Maingi, R.; Majeski, R.; et al.
Abstract: Recent experiments in the lithium tokamak experiment- β (LTX- β ) have extended the duration, performance, operating conditions, and diagnosis of the flat-temperature profile, low-recycling regime first observed in LTX. As expected, Li retains hydrogen and suppresses edge neutral cooling, allowing increased edge electron temperature, roughly equal to the core T e . Flat temperature profiles had been obtained transiently in LTX, as the plasma density decayed following the cessation of edge gas puffing. Careful control over the fueling in LTX- β has now been shown to sustain the flat T e profile and hot edge unique to the low-recycling regime for multiple confinement times in high performance discharges with decaying or steady density. With low density, the flat T e profile is also seen to extend into the scrape-off layer. Neutral beam heating is observed in target discharges with relatively flat electron temperature profiles ( T edge ∼ T core /2), though beam heating is stronger in discharges with higher fueling, higher density, and depressed edge T e . Beam heating produces additional peaking of the T e profile, without degradation of the energy confinement time. Neutral beam heating of target discharges with relatively flat electron temperature profiles similarly results in broad beam heated temperature profiles. Energy confinement in LTX- β generally compares favorably to ohmic and H-mode scalings, frequently exceeding them by factors of 2–4. New and improved diagnostics in LTX- β enable better characterization of this unique regime, including measurements of ion temperature and high field side Thomson scattering profiles. As an initial step toward characterizing turbulence with no T e gradient and roughly equal density and pressure gradient, core fluctuation spectra have been measured in peaked T e discharges using far-forward scattering and fluctuation reflectometry.